1999
DOI: 10.1577/1548-8659(1999)128<1230:spoyfs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Stranding Potential of Young Fishes Subjected to Simulated Vessel-Induced Drawdown

Abstract: During early life stages, fish in the Mississippi River system may become stranded by shoreline drawdowns induced by the passage of commercial vessels. We examined the stranding of larval shovelnose sturgeon Scaphirhynchus platorynchus, paddlefish Polyodon spathula, and bigmouth buffalo Ictiobus cyprinellus and of juvenile blue catfish Ictalurus furcatus, largemouth bass Micropterus salmoides, and bluegill Lepomis macrochirus in a laboratory flume. Stranding was measured at three vertical drawdown rates (0.76,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Higher beach stranding occurs more frequently on gently sloping banks than on steeper gravel bars (Adams et al 1999;Bradford et al 1995;Hunter 1992), especially with slopes that are \5% (Bauersfeld 1978;Beck and Associates 1989;Hunter 1992;Olson 1990;Pflug et al 1989). In the Cowlitz River (California USA), most of the Chinook salmon (Oncorhynchus tshawytscha) fry stranding occurred on gravel bars of \2% slope (Bauersfeld 1978).…”
Section: Strandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher beach stranding occurs more frequently on gently sloping banks than on steeper gravel bars (Adams et al 1999;Bradford et al 1995;Hunter 1992), especially with slopes that are \5% (Bauersfeld 1978;Beck and Associates 1989;Hunter 1992;Olson 1990;Pflug et al 1989). In the Cowlitz River (California USA), most of the Chinook salmon (Oncorhynchus tshawytscha) fry stranding occurred on gravel bars of \2% slope (Bauersfeld 1978).…”
Section: Strandingmentioning
confidence: 99%
“…Species that occur in littoral and backwater areas that either swim with the current or passively drift with the current are less likely to be stranded. While they may swim or drift up into newly flooded areas during a pulse, they will swim or drift back toward the main channel with receding water, while the young of main-channel fishes that are positively rheotaxic are more likely to swim against the flow of receding water and become stranded (Adams et al 1999). …”
Section: Strandingmentioning
confidence: 99%
“…Bowers and de Szalay (2005) suggested that irregular fluctuations in water level resulting from wind-driven seiches kept zebra mussels from colonizing shallow substrates along the shore of Lake Erie. Winddriven waves or wakes can strand young fish on the shore and dewater nests (Adams et al 1999;Wolter and Arlinghaus 2003). The same effects can be produced by rapidly falling water levels downstream of peaking hydropower dams (Cushman 1985).…”
Section: Hydrologic Regimementioning
confidence: 99%
“…If it is not protected, erosion of the shoreline will disrupt the terrestrial side of the shore zone and increase turbidity on the aquatic side of the shore zone, further endangering submerged vegetation and the fauna that it supports. High inputs of energy may prevent animals from maintaining desired positions in the water or even wash them onto the shore (Adams et al 1999;Wolter and Arlinghaus 2003). Fig.…”
Section: Increasing Inputs Of Physical Energymentioning
confidence: 99%
“…The floodplain slope in our tests was set to 10°( ca. 19% grade), while other investigators measured increased stranding rates of small fishes using more gradual slopes (Hunter 1992;Bradford et al 1995;Adams et al 1999). Both the limited (ca.…”
Section: Discussionmentioning
confidence: 96%